Interventions for cancer-related pain: Protocol of an umbrella systematic review and network meta-analysis - Xu, Tao (Medicine (Baltimore), 2019)
BACKGROUND: Several treatments are beneficial for patients with cancer-related pain (CRP), and there are numbers of systematic reviews evaluating the effectiveness and safety of these treatments. However, the overall quality of the evidence has not been quantitatively assessed. The aim of this study is to overcome the inconclusive evidence about the interventions of CRP. METHODS: We will perform an umbrella systematic review to identify eligible randomised controlled trials (RCTs). A comprehensive literature search will be conducted in MEDLINE, EMBASE, and the Cochrane library for systematic reviews, meta-analyses and RCTs. We will describe the general information of the RCTs for participants, interventions, outcome measurements, comparisons, and results. Network meta-analysis will be developed to determine the comparative effectiveness of the treatments. RESULTS: The result of this network meta-analysis will provide direct and indirect evidence of treatments for CRP. CONCLUSION: The conclusion of our study will help clinicians and CRP patients to choose suitable treatment options. ETHICS AND DISSEMINATION: Formal ethical approval is not required, as the data are not individualized. The findings of this systematic review will be disseminated in a peer-reviewed publication and/or presented at relevant conferences. PROSPERO REGISTRATION NUMBER: CRD42019131721.